Generalised Periodontitis: A Behavioural Management. - Nur Ayman Abdul Hayei; Nor Haliza Mat Baharin (USIM Press, 2024)
Vol. 7 (2021): Special Issue on Clinical Scenarios In Medicine, A Malaysian Experience (Case Report)